Lao People's Democratic Republic : Technical Assistance Report-Government Finance Statistics and Public Sector Debt Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2021)
This technical assistance (TA) report on government finance statistics (GFS) covers the remote TA to the Ministry of Finance (MOF) during September 21-October 2 and December 14-18, 2020 and March 9-13 and April 19-23, 2021 (which was extended to May 2021). These peripatetic activities were conducted remotely due to the travel restrictions resulting from the COVID-19 situation. This report documents the main achievements from these activities. These activities were part of the GFS and Public Sector Debt Statistics (PSDS) project funded by the Government of Japan (JSA3) and implemented by the IMF Statistics Department (STA) and the IMF Capacity Development Office in Thailand (CDOT).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy